Perlindungan Hukum terhadap Investor dalam Transaksi Jual Beli Saham melalui Perusahaan Sekuritas Ilegal Berbasis Online - I Gusti Ayu Andara; I Nyoman Putu Budiartha; Desak Gede Dwi Arini (Jurnal Konstruksi Hukum, 2022)
The development of internet technology that is increasingly developing affects the stock investment sector related to financial digitization. Indonesia is a developing country that uses technology to create innovation in economic products. The ease of investing online certainly makes it easier for people to carry out investment activities. Moreover, with all the conveniences and increasingly sophisticated technology, causing criminals who harm others by using technology as a medium. The purposes of this study are to analyze the form of legal protection for investors in buying and selling shares through online-based illegal securities companies and the forms of liability of illegal securities companies to investors who are harmed by online share buying and selling transactions. This legal research method is normative with a statutory and conceptual approach. The sources of law used are primary and secondary sources of law. The technique of collecting legal materials is carried out in the library which is then analyzed using descriptive analysis techniques. The results showed that . Legal protection is carried out by means of preventive (prevention) and repressive (sanctioning). Criminal, civil and administrative sanctions will be accepted as a form of responsibility for online-based illegal securities companies. the responsibility of online-based illegal securities companies that can be subject to criminal, civil and administrative sanctions.